2008
DOI: 10.1007/s11239-008-0299-6
|View full text |Cite
|
Sign up to set email alerts
|

Time course of thrombosis and fibrinolysis in total knee arthroplasty with tourniquet application. Local versus systemic activations

Abstract: The use of tourniquet in total knee arthroplasty causes local thrombogenic and fibrinolytic activity, but without influences in the systemic circulation. Systemic activations in thrombosis and fibrinolysis start when local mediators from the injured limb are released after tourniquet deflation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 25 publications
0
41
0
4
Order By: Relevance
“…Although evidence is emerging that even mild episodes of limb ischemia might elicit pathologic changes like increased leukocyte adhesiveness, endothelial damage, and activation of a procoagulatory state with possible risk of thrombogenesis [10], the clinical relevance of these findings remains unknown. In a recent clinical study, Reikerås et al found significant local thrombogenic and fibrinolytic activity in the operative leg after tourniquet deflation but no significant systemic impact [18]. Moreover, it was previously suggested that a hypercoagulative state is more likely to appear in TKA cases in which no tourniquet is used [1].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although evidence is emerging that even mild episodes of limb ischemia might elicit pathologic changes like increased leukocyte adhesiveness, endothelial damage, and activation of a procoagulatory state with possible risk of thrombogenesis [10], the clinical relevance of these findings remains unknown. In a recent clinical study, Reikerås et al found significant local thrombogenic and fibrinolytic activity in the operative leg after tourniquet deflation but no significant systemic impact [18]. Moreover, it was previously suggested that a hypercoagulative state is more likely to appear in TKA cases in which no tourniquet is used [1].…”
Section: Discussionmentioning
confidence: 98%
“…Although we hypothesized that preconditioning may positively influence the level of local inflammation at the site of surgery as suggested by previous experimental evidence [15], no such data were available from our study at the time. Moreover, changes in systemic levels of coagulation activity were not measured in this study, and there is conflicting evidence about the systemic impact of tourniquet maneuvers on coagulation status [10,18].…”
Section: Introductionmentioning
confidence: 88%
“…This enhances local fibrinolysis and leads to increased postoperative blood loss, especially in the first 6 hours after tourniquet release (25). In the present study, we administrated TXA just before surgery rather than on deflation of the tourniquet.…”
Section: Discussionmentioning
confidence: 98%
“…However, the fibrinolytic system was activated due to surgery trauma postoperatively and was 90 deteriorated for tourniquet application. Long time ischemia of lower extremity activated plasminogen 91 into plasmin, promoted fibrinolysis and increased blood loss after tourniquet deflation [19]. TA was an 92 artificial synthetic antifibrinolytic agent that could effectively inhibit the fibrinolysis and thus reduced 93 the perioperative blood loss.…”
mentioning
confidence: 99%